Особливості стилю як елементу авторської свідомості у поезії Богдана-Ігоря Антонича - Рубан, Я. (Літературознавчі обрії. Праці молодих учених, 2010)
The features of style are examined in this article as the element of author’s consciousness on the basis of poetry by B.-I. Antonych, in particular, ways of organization of text material, such as threading synonymous or syntactic constructions of the same type, synthesis of metaphors, combination of different types of perception, and others. This research is an attempt to trace changes in style and methods of reality reflection in the process of author’s perception development.